Pengaruh Kebijakan Fiskal dan Dana Perimbangan terrhadap Belanja Daerah: Studi pada Pemerintah Kabupaten/Kota di Sumatera Selatan - Harry Yulvian; Rita Martini; Rosy Armaini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Research on the effect of fiscal policy and balancing funds on expenditures in the government of the City/Regency of South Sumatra is the purpose of this study. City/Regency Provincial Government Budget Realization Report. South Sumatra 2019-2021 is the main source of secondary data for this research. The saturated sample approach is the one used for the sampling process. Classical assumption test, multiple linear regression analysis test, and hypothesis testing are the analyzes used in this study. The tool used by the SPSS 26 application, and the results indicate that PAD, DBH, and DAU have a significant positive effect on regional spending, while DAK has no effect on City / District government spending. South Sumatra Keywords: Regional Expenditure; Balance Fund; Fiscal Policy